Clinical implications of the tiotropium/olodaterol inhaler for patients with chronic obstructive pulmonary disease. Issue 6 (18th August 2018) - Ferguson, Gary T.; Dalby, Richard N.
ABSTRACT: Oral inhalation is the recommended delivery method of medications for the treatment of patients with chronic obstructive pulmonary disease (COPD). However, patients may struggle when using the various available inhaler platforms, and, as a result, may fail to achieve the benefit of the prescribed medication. Propellant-based, pressurized metered-dose inhaler and powder-based, dry powder inhaler devices are currently the most commonly prescribed delivery systems. Each of these devices has its own advantages and challenges. The Respimat® Soft Mist™ inhaler (SMI) (Boehringer Ingelheim) is a delivery system that incorporates features intended to improve orally inhaled drug delivery to these patients. These features include simple device actuation, patient inspiratory effort-independent aerosol generation, and a slower spray emission with a longer spray duration, helping to mitigate issues with precise aerosol release and breath coordination. We review the clinical trials assessing lung deposition, efficacy, and safety, and patient satisfaction for the Respimat® SMI. These data indicate that the Respimat® SMI is a device capable of delivering a consistent, clinically effective dose of medication that patients can use and prefer, which may provide significant clinical benefits for patients with COPD.